2012
DOI: 10.1037/a0028884
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of school readiness among head start children: Meaningful within-group variability during the transition to kindergarten.

Abstract: This study is a population-based investigation of children's school readiness with a national sample of low-income children, utilizing data from the Family and Children's Experiences Survey (FACES;-2003. Guided by a developmental ecological framework, we posed 3 research questions: (a) How do children's early school readiness skills in the social and cognitive domains overlap (as they enter preschool)? (b) Do these configurations of school readiness skills meaningfully predict children's school adjustment by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 71 publications
2
18
1
Order By: Relevance
“…Although previous investigations with representative and more high-risk samples have reported that social competence is associated with academic functioning at first grade, the current findings with a large, national sample extend this work through fifth grade (Hair et al, 2006; PATTERNS OF EARLY READING AND SOCIAL SKILLS Konold & Pianta, 2005;McWayne et al, 2012). Taken together, these findings provide strong descriptive evidence of how children with similar academic abilities (in reading, in our case) who vary in early social competence differ in mean levels of later academic success.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Although previous investigations with representative and more high-risk samples have reported that social competence is associated with academic functioning at first grade, the current findings with a large, national sample extend this work through fifth grade (Hair et al, 2006; PATTERNS OF EARLY READING AND SOCIAL SKILLS Konold & Pianta, 2005;McWayne et al, 2012). Taken together, these findings provide strong descriptive evidence of how children with similar academic abilities (in reading, in our case) who vary in early social competence differ in mean levels of later academic success.…”
Section: Discussionsupporting
confidence: 56%
“…They found that preschoolers who had average cognitive abilities but high social competence and few behavior problems performed well in first grade, whereas preschoolers who had poor social skills and behavioral skills in preschool did poorly. Other studies have found similar results, suggesting that early social skills may serve as a protective factor for later outcomes when children have moderate or low academic=cognitive abilities in early childhood but may be less important for more academically ready children (Bierman, Torres, Domitrovich, Welsh, & Gest, 2009;Hair et al, 2006;Konold & Pianta, 2005;McWayne et al, 2012;Sabol & Pianta, 2012). Variable-centered approaches, even including interactions, may not detect these patterns.…”
Section: Subgroup Approaches To Understanding Child Developmentmentioning
confidence: 56%
See 1 more Smart Citation
“…The enhancement of children's social skills is one of the most important outcomes of early childhood education (Gregoriadis, Grammatikopoulos, & Zachopoulou, 2013;Serpell & Mashburn, 2012) because preschoolers' social skills are related to school readiness and adjustment (Denham, 2006;Rimm-Kaufman, Pianta, & Cox, 2000), in order to later succeed in academic achievement (McWayne, Cheung, Green Wright, & Hahs-Vaughn, 2012;Oades-Sese, Esquivel, Kaliski, & Maniatis, 2011) and to peer acceptance (Lindsey, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for children who come from low-income households and are thought to be at risk for difficulties in adjusting to formal schooling (McWayne, Cheung, Green Wright, & Hahs-Vaughn, 2012). Engagement with peers can be influential in several domains (emotional, cognitive, social) that are important for school competence (Rubin, Bukowski, & Parker, 2006).…”
mentioning
confidence: 99%